The Effect Between Behavioral Biases and Investment Decisions Moderated by Financial Literacy on the Millennial Generation in Jakarta - Natasya Natasya; Dyah Hayu Kusumastuti; Widya Alifia; Farah Margaretha Leon (The Accounting Journal of Binaniaga, 2022)
Abstract: The purpose of this research was to analyze the effect of financial literacy and behavioral bias on investment decisions in the millennial generation in DKI Jakarta. This research uses quantitative data by distributing questionnaires. The population of this research is people who live in DKI Jakarta and its surroundings. There are as many as 125 respondents in the research conducted. The data collection method used a questionnaire and for the data analysis method in this research using the SEM analysis tool. The findings of this research indicate that overconfidence bias and risk-aversion bias have a significant effect on investment decisions. Meanwhile, herding bias, disposition effect, and financial literacy have no significant effect on investment decisions